Management of Persistent Postnasal Drip Without Sinus Affection (American Journal of Interdisciplinary Research and Innovation, 2024)
Persistent postnasal drip (PPND), characterized by chronic mucus sensation in the throat without evident sinus involvement, poses challenges in otolaryngology. This study aimed to evaluate low dose, long duration Clarithromycin’s efficacy in managing PPND symptoms, addressing the limitations of existing therapies. A prospective, randomized, controlled trial was conducted with 50 participants (18-65 years) diagnosed with PPND but without sinus pathology (proved by sinus clear CT Paranasal sinus scans). They received either Clarithromycin (250 mg daily) or a placebo for 12 weeks. Validated assessment tools, such as the nasal symptom score (NSS), visual analog scale (VAS), and Sino-nasal outcome test-22 (SNOT-22), measured treatment outcomes. Current therapies addressing associated symptoms exhibit limited efficacy, prompting the need for novel treatment strategies. The study revealed a significant improvement in PPND symptoms with low-dose, long-duration Clarithromycin treatment. Participants exhibited reduced throat-clearing frequency, cough episodes, and subjective mucus sensation. Objective assessments showed enhanced nasal pathology and mucociliary clearance post-treatment. Low-dose, long-duration Clarithromycin treatment demonstrated promising efficacy in ameliorating PPND symptoms and improving quality of life without sinus involvement. These findings emphasize the potential therapeutic role of macrolides in addressing PPND’s underlying pathophysiology. Further research, including larger trials, is essential to validate these outcomes and establish effective clinical guidelines for managing PPND.